2009
DOI: 10.1111/j.1365-2567.2009.03087.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human peripheral blood monocytes with apoptotic polymorphonuclear cells

Abstract: SummaryMacrophages have the potential to recognize apoptotic neutrophils and phagocytose them while the same function for monocytes is uncertain. In fact, early findings indicated that monocytes started to phagocytose neutrophils on the third day of differentiation to macrophages. Here we show, using flow cytometry and confocal microscopy, that peripheral blood monocytes phagocytose apoptotic but not freshly isolated granulocytes. Recognition of apoptotic cells is predominantly connected with CD16 + monocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 69 publications
6
43
0
Order By: Relevance
“…To test this possibility, we analyzed changes in apoptotic death in neutrophils from human and murine origin, with the finding that the presence of this metalloprotease triggered an increment in their apoptosis. In this regard, previous works have described the ability of proteins containing thrombospondin type-1 repeats to interact with surface proteins such as CD36 and CD47 (30,31), that can modulate neutrophil death and clearance (32,33). Hence, it is conceivable a model in which ADAMTS-12 could participate in similar protein interactions through its thrombospondin domains.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we analyzed changes in apoptotic death in neutrophils from human and murine origin, with the finding that the presence of this metalloprotease triggered an increment in their apoptosis. In this regard, previous works have described the ability of proteins containing thrombospondin type-1 repeats to interact with surface proteins such as CD36 and CD47 (30,31), that can modulate neutrophil death and clearance (32,33). Hence, it is conceivable a model in which ADAMTS-12 could participate in similar protein interactions through its thrombospondin domains.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main jobs of macrophages at the site of infection is to engulf and destroy infected neutrophils in order to keep the intracellular components from damaging host tissue. Apoptotic neutrophils have on the outer membrane specific surface proteins and phospholipids, such as phosphatidylserine (PS), which signal to macrophages that they need to be taken up (14). Studies have shown that macrophage uptake of apoptotic cells can be either harmful or helpful for the survival of intracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing apoptosis have unique characteristics, including DNA fragmentation and blebbing of the membrane. On the outer membrane, they also have specific surface proteins and phospholipids, such as phosphatidylserine (PS), which signal to phagocytic cells that they need to be taken up (14). The main cells in charge of phagocytizing apoptotic cells are macrophages.…”
mentioning
confidence: 99%
“…26 CD36 is an 88-kDa transmembrane glycoprotein expressed in a wide variety of cell types, such as those of the microvascular endothelium, "professional" phagocytes (including MK, dendritic cells, and microglia) and retinal pigment epithelium, erythroid precursors, hepatocytes, adipocytes, cardiac and skeletal myocytes, and specialized epithelia of the breast, kidney, and gut. 27 Accumulating evidence shows that CD36 recognizes many types of ligands, including thrombospondin, 28 Plasmodium falciparum, 29,30 bacterial cell wall components, 31 phosphatidylserine, and oxidized phosphatidylserine that are expressed on the surface of apoptotic cells, 32 and oxLDL, 33 among others. The multivariate ligand recognition of CD36 allows it to exert several functions, depending on the cell type.…”
Section: Introductionmentioning
confidence: 99%